2006
DOI: 10.1002/masy.200690027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Hysteresis Behaviour of Multigraft Copolymers

Abstract: Summary: PS-PI multigraft copolymers with tri-tetra-and hexafunctional polystyrene branch points have been studied to investigate the influence of molecular architecture on morphological and tensile properties and to find novel material concepts. It was found that the morphological behaviour of these grafted copolymers can be predicted using theoretical approaches. The number of branch points, however, greatly influences the long-range order of microphase separation. Additionally, two new parameters for adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 19 publications
2
68
0
Order By: Relevance
“…By further coupling the PS macromonomer with difunctional living polyisoprene anions, centipede‐like multigraft copolymers with two PS at the same branching points was prepared. Using a similar strategy but with different coupling agents such as methyltrichlorosilane or 1,6‐bis(trichlorosilyl)‐hexane (“hexachlorosilane”), comb‐ or barbwire‐like multigraft copolymers with one or four PS chains at each branching points were synthesized …”
Section: Regularly Spaced Multigraft Copolymers Synthesized By Chloromentioning
confidence: 99%
See 3 more Smart Citations
“…By further coupling the PS macromonomer with difunctional living polyisoprene anions, centipede‐like multigraft copolymers with two PS at the same branching points was prepared. Using a similar strategy but with different coupling agents such as methyltrichlorosilane or 1,6‐bis(trichlorosilyl)‐hexane (“hexachlorosilane”), comb‐ or barbwire‐like multigraft copolymers with one or four PS chains at each branching points were synthesized …”
Section: Regularly Spaced Multigraft Copolymers Synthesized By Chloromentioning
confidence: 99%
“…Since the final coupling reaction employs a step‐growth mechanism, the prepared multigraft copolymers generally have a PDI around 2. Using solvent/nonsolvent fractionation procedures, one can readily isolate multigraft copolymers with different average numbers of branch points and PDI (PDI ≈ 1.2), providing ideal materials with which to study the influence of number of branch points on a wide range of properties such as morphologies, chain dynamics, mechanical properties, and hysteresis behaviors . General nomenclature of these material is MG‐ x ‐ y ‐ z , where MG stands for regular multigraft, x (3, 4, and 6) is the junction point functionality, y refers to the volume percentage of PS, and z represents the average number of junction points per molecules calculated from NMR spectra.…”
Section: Regularly Spaced Multigraft Copolymers Synthesized By Chloromentioning
confidence: 99%
See 2 more Smart Citations
“…Structure-property relationship of these graft copolymers was elucidated by characterizing morphology [76,77] and mechanical properties [78][79][80] of grafted polymers with different compositions (14-23 vol% of PS) and architectures (trifunctional, tetrafunctional, and hexafunctional junction points). From their research, multigraft polymers with tetrafunctional junction points showed 1550% strain at break which is 500% higher than that for the commercial product Kraton 1102.…”
Section: Graft Copolymer-type Tpesmentioning
confidence: 99%